Analysis of Gedongsongo Temple Waste Management in The Development of Sustainable Tourism Destinations - Mesyrawati Putri Laia; Pranoto (University of Merdeka Malang, 2025)
This research was conducted in the Gedongsongo Temple Area which aims to determine and analyze the waste management system, identify the role of stakeholders, explore management challenges, formulate sustainable management strategies. Data collection techniques used interviews, field observations, documentation Focus Group Discussion with Temple Managers, Cleaning Officers, Traders, Community Leaders, Visitors, Head of the Semarang Regency Tourism Office as research informants. The data obtained were then analyzed by means of Data Reduction, Data Presentation, Conclusion Drawing, and Triangulation. Then the data that has been analyzed is then carried out Data Validity using Source Triangulation, Method Triangulation, Member Checking, and Expert Review. The results of the study obtained are Waste Management in the Gedongsongo Temple Area with stakeholders in the development of sustainable destinations, both Temple Managers, Cleaning Officers, Traders, Community Leaders, Visitors, Head of the Semarang Regency Tourism Office is still running in accordance with the existing structure and regulations and the level of awareness of tourism destination stakeholders, especially Gedongsongo Temple, is still running well.